How basic-level objects facilitate question-asking in a categorization task - Ruggeri, Azzurra; Feufel, Markus (Frontiers in Psychology, 2015)
The ability to categorize information is essential to everyday tasks such as identifying the cause of an event given a set of likely explanations or pinpointing the correct from a set of possible diagnoses by sequentially probing questions. In three studies, we investigated how the level of inclusiveness at which objects are presented (basic-level versus subordinate-level) influences children’s (7 and 10-year olds) and adults’ performances in a sequential binary categorization task. Study 1 found a robust facilitating effect of basic-level objects on the ability to ask effective questions in a computerized version of the Twenty Questions game. Study 2 suggested that this facilitating effect might be due to the kinds of object-differentiating features participants generate when provided with basic-level as compared to subordinate-level objects. Study 3 ruled out the alternative hypothesis that basic-level objects facilitate the selection of the most efficient among a given set of features.